Wholly‐owned vs. collaborative ventures for diversifying financial services - Ingham, Hilary; Thompson, Steve (Strategic Management Journal, 1994)
Abstract Recent empirical work has supported the Penrose‐Teece view that firms diversify to exploit fully specific assets or capabilities. Where transactions costs permit, these economies of scope may be realized via input supply contracts among producers. However, asset specificities frequently create transactions costs which discourage market contracting and leave firms with a choice between collaborative ventures and wholly‐owned new entry. This research uses the natural experiment of financial services deregulation to explore the collaborative‐own entry choice for 292 new entries in 13 financial product markets. The results generally support our maintained hypotheses that specificity encourages full ownership while collaboration is used to ease a resource constraint.